A remarkable new species of Rhaphium Meigen (Diptera, Dolichopodidae) from Sri Lanka STEFAN NAGLIS (Switzerland) & PATRICK GROOTAERT (Belgium) - Naglis, Stefan; Grootaert, Patrick (Zootaxa, 2011)
Rhaphium srilankensis sp. nov. is newly described from Sri Lanka. It is distinguished from all congeners by the total absence of an arista in males. The new species is the first Oriental record of Rhaphium outside of China. A key to the Oriental genera of Rhaphiinae is provided.